Microstructural investigation and machining performance of NbC-Ti(C0.5N0.5) matrix cermets. (November 2019) - Huang, S.G.; Nie, H.B.; Guo, X.Y.; Vleugels, J.; Huang, J.H.; Mohrbacher, H.; Rajendhran, N.K.; Sukumaran, J.; De Baets, P.; Cannizza, E.; Woydt, M.
Abstract: In this study, Ni or Co + Ni bonded NbC matrix cermets with secondary carbides (Mo2 C and WC) as well as Ti(C0.5 N0.5 ) were prepared by liquid phase sintering at 1450 °C in vacuum. Detailed microstructural investigation was performed by SEM, EPMA and XRD analysis. The microstructure, mechanical properties as well as the C45 (HB140) steel turning performance of the cermets were investigated, and compared with a commercial Ti(C0.5 N0.5 ) based cutting insert. The sintering results indicated that the partial substitution of NbC by Ti(C0.5 N0.5 ) had a significant effect on the core-rim microstructure and refinement of NbC solution grains, as well as improved mechanical properties of the NbC-Ti(C0.5 N0.5 ) cermets. The phase constitution and composition of the cermets were supported by thermodynamic equilibrium calculations. All sintered cermets were composed of a fcc solid solution metal binder and a cubic core-rim NbC based solution phase, as well as an independent N-rich Ti(C, N) phase. The NbC-Ti(C0.5 N0.5 ) and Ti(C0.5 N0.5 ) matrix cermets had a comparable HV30 of 1500–1600 kg/mm 2 and a similar fracture toughness of 8.0 MPa m 1/2 . Highlights: Full dense Ni or Co + Ni bonded NbC matrix cermets with Mo2 C and WC as well as Ti(C0.5 N0.5 ) were prepared by liquid phase sintering at 1450 °C in vacuum. The sintering results indicated that the partial substitution of NbC by Ti(C0.5 N0.5 ) had a significant effect on the microstructural refinement, the formation of a core-rim microstructure and improved mechanical properties of the NbC-Ti(C0.5 N0.5 ) cermets. The NbC-Ti(C0.5 N0.5 ) and Ti(C0.5 N0.5 ) matrix cermets had a comparable HV30 of 1500–1600 kg/mm 2 and a similar fracture toughness of 8.0 MPa m 1/2 . The flank wear during dry turning of C45 steel decreased with increasing Ti(C0.5 N0.5 ) content. The 32 and 42 wt% Ti(C0.5 N0.5 ) containing NbC-based inserts exhibited a respectively comparable and lower flank wear than a commercial Ti(C0.5 N0.5 )-based insert.